Timing and methods of frailty assessments in geriatric trauma patients: A systematic review. Issue 11 (November 2019) - Cubitt, Mya; Downie, Emma; Shakerian, Rose; Lange, Peter W.; Cole, Elaine
Highlights: Although evidence gaps remain, frailty assessment in geriatric trauma identifies patients at risk of adverse outcomes, including mortality. Demonstrating cost effective geriatric specific trauma care will rely on consistent measurement of long-term geriatric specific outcomes. The optimal early measurement of frailty and its subsequent trajectories offer compelling clinical and research priorities in geriatric trauma. Abstract: Introduction: The trauma population is aging and better prognostic measures for geriatric trauma patients are required. Frailty rather than age appears to be associated with poor outcomes. This systematic review aimed to identify the optimum frailty assessment instrument and timing of assessment in patients aged over 65 years admitted to hospital after traumatic injury. The secondary aim was to evaluate outcomes associated with frailty in elderly trauma populations. Methods: This systematic review was registered with the PROSPERO International Prospective Register of Systematic Reviews (CRD42018090620). A MEDLINE and EMBASE literature search was conducted from inception to June 2019 combining the concepts of injury, geriatric, frailty, assessment and prognosis. Included studies were in patients 65 years or older hospitalised after injury and exposed to an instrument meeting consensus definition for frailty assessment. Study quality was assessed using criteria for review of prognostic studies combined with a GRADE approach. Results: Twenty-eight papers met inclusion criteria. Twenty-eight frailty or component instruments were reported, and assessments of pre-injury frailty were made up to 1-year post injury. Pre-injury frailty prevalence varied from 13% (13/100) to 94% (17/18), with in-hospital mortality rates from 2% (5/250) to 33% (6/18). Eleven studies found an association between frailty and mortality. Eleven studies reported an association between frailty and a composite outcome of mortality and adverse discharge destination. Generalisability and assessment of strength of associations was limited by single centre studies with inconsistent findings and overlapping cohorts. Conclusions: Associations between frailty and adverse outcomes including mortality in geriatric trauma patients were demonstrated despite a range of frailty instruments, administering clinicians, time of assessment and data sources. Although evidence gaps remain, incorporating frailty assessment into trauma systems is likely to identify geriatric patients at risk of adverse outcomes. Consistency in frailty instruments and long-term geriatric specific outcome measures will improve research relevance. Level of evidence: : Level III prognostic.